Genomic library construction and inheritance patterns analysis of F1 grouper hybrid: Epinephelus coioides X Epinephelus lanceolatus - Lim, Ming Lee (2012)
The Fl hybrid of Epinephelus coioides and Epinephelus lanceolatus is a fast growing and well tolerance to crowing stress. An understanding of the underlying genomic inheritance patterns facilitates our understanding of the association between phenotypes and genotypes in Fl hybrid. A panel of thirty molecular markers was developed based on the partial small insert genomic library that constructed previously using shotgun approach. Testing against parental genotype and closely related grouper species revealed two markers which were unique to the original Fl hybrid; none of the primers amplified in the groupers Epinephelus fuscoguttatus and Epinephe/us coral/icola; seventeen markers were shared between Epinephe/us coioides and Epinephelus lanceolatus, five were unique to Epinephe/us coioides and seven were unique to Epinephelus lanceolatus including two heterozygous markers. These markers can be utilized to determine inheritance pattern of this Fl grouper hybrids and also genetic similarity and differentiation among all the tested groupers.